Characteristics of synovial fluid required for optimization of lubrication fluid for biotribological experiments - Galandáková, Adéla; Ulrichová, Jitka; Langová, Kateřina; Hanáková, Adéla; Vrbka, Martin; Hartl, Martin; Gallo, Jiří (Journal of biomedical materials research. Part B, Applied biomaterials, 2017)
Wear testing of total joint replacement (TJR) is mandatory in preclinical testing before implantation of TJR into the human body. Testing is governed by current international standards that recommend bovine serum (BS) as a lubricating fluid to replace synovial fluid (SF). Recently, the use of BS has been criticized because of differences in content, fluid characteristics, and nonhuman origin. As a result, a more realistic lubricant mimicking SF is needed. To define SF composition, we analyzed SF obtained during revisions of total hip and knee arthroplasties and compared it with SF obtained during primary arthroplasties and from patients without TJR. Samples were acquired from 152 patients. We found that the median total protein concentration for all SF was 36.8 mg/mL, which is significantly higher than concentrations currently recommended by the ISO standards. The γ-globulin concentration was significantly higher and the phospholipid concentration significantly lower in patients with revision of TJR compared with patients without TJR. No significant difference was found in hyaluronic acid concentration and viscosity among the groups. Our results support the need to improve the definition of a more clinically relevant wear testing lubricant in the ISO standards. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1422-1431, 2017.
Keywords: synoviální tekutina; náhrada kyčelního kloubu; lidé; Middle Aged; Adult; Lubricants; Arthroplasty, Replacement, Knee; Female; Synovial Fluid; Phospholipids; gama-globiny; biomimetické materiály; Humans; lubrikanty; Biomimetic Materials; gamma-Globins; lidé středního věku; mužské pohlaví; fosfolipidy; ženské pohlaví; Male; totální endoprotéza kolene; Aged; Arthroplasty, Replacement, Hip; dospělí; senioři